2008
DOI: 10.1016/j.taap.2007.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of caveolin-1 expression, nitric oxide production and tissue injury by tumor necrosis factor-α following ozone inhalation

Abstract: Alveolar macrophages (AM) and inflammatory mediators including nitric oxide and peroxynitrite contribute to ozone-induced lung injury. The generation of these mediators is regulated, in part, by the transcription factor NF-κB. We previously demonstrated a critical role for NF-κB p50 in the ozone-induced injury. In the present studies mechanisms regulating NF-κB activation in the lung after ozone inhalation were analyzed. Treatment of wild type (WT) mice with ozone (0.8 ppm, 3 h) resulted in a rapid increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 64 publications
5
17
0
Order By: Relevance
“…Additionally, knockout studies in mice have suggested that TNF-a deletion exerts a neuroprotective function. 36,37) In this study, ELISA analysis revealed that TNF-a production was significantly inhibited by 1 mg/ml NS (Fig. 2), which indicates that NS exerts its effects via a pathway that protects cells from neuroinflammatory cytokine regulation (Fig.…”
Section: Fig 2 Dose-dependent Inhibitory Effects Of Nelumbinis Semesupporting
confidence: 50%
“…Additionally, knockout studies in mice have suggested that TNF-a deletion exerts a neuroprotective function. 36,37) In this study, ELISA analysis revealed that TNF-a production was significantly inhibited by 1 mg/ml NS (Fig. 2), which indicates that NS exerts its effects via a pathway that protects cells from neuroinflammatory cytokine regulation (Fig.…”
Section: Fig 2 Dose-dependent Inhibitory Effects Of Nelumbinis Semesupporting
confidence: 50%
“…The proinflammatory cytokine TNFα and the profibrotic cytokine TGFβ have major roles in inflammation and fibrosis in scleroderma1 and have been shown to inhibit caveolin-1 expression in other cell types 18 19 23. We therefore examined the possibility that these treatments might inhibit caveolin-1 expression in monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It was described that caveolin-1 has a protective role during inflammation by suppressing the production of pro-inflammatory mediators (e.g. TNF␣ and IL-6) and promoting the anti-inflammatory response in macrophages (Ben et al, 2013;Fakhrzadeh, 2008;Wang et al, 2006). One of the few known facts about the connection of caveolins with signal transduction is the initiation of MAPK pathways after stimulation of macrophages by classical activators (Feng et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…and are responsible for production of a wide spectrum of pro-inflammatory mediators (e.g. NO and tumor necrosis factor alpha, TNF␣) (Burke et al, 2003;Talks et al, 2000;Ben et al, 2013;Laskin et al, 2010;Fakhrzadeh, 2008;Parameswaran and Patial, 2010). Importantly, when recruited to tissue sites of infection or inflammation, macrophages immediately encounter a decreasing oxygen gradient, which leads to stabilization of hypoxia inducible factor-1 alpha (HIF-1␣) protein.…”
mentioning
confidence: 99%